2007
DOI: 10.1139/p07-038
|View full text |Cite
|
Sign up to set email alerts
|

Height-dependent meteor temperatures and comparisons with lidar and OH measurements

Abstract: A new method is introduced that allows meteor radars to potentially produce height-dependent temperatures, rather than simply averages over the meteor region. The method is applied to data from the Clovar radar, near London, Ontario, and then a three-way comparison between Rayleigh lidar temperatures, hydroxyl temperatures, and meteor temperatures is undertaken. The three methods prove to be complementary. The OH measurements have good accuracy, but suffer slightly from lack of precise knowledge about their he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…Using the first-order polynomial has a limitation to determine only an average temperature in the range of the meteor heights and also requires a mean temperature gradient at the height. However, it has been reported in a number of studies that the mesospheric temperatures estimated from this method are relatively consistent with other ground-based temperature measurements (Singer et al, 2003Hocking et al, 2004Hocking et al, , 2007Holdsworth et al, 2006;Stober et al, 2008). For details on the advantage and limitation of this method refer to Hocking et al (2004).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Using the first-order polynomial has a limitation to determine only an average temperature in the range of the meteor heights and also requires a mean temperature gradient at the height. However, it has been reported in a number of studies that the mesospheric temperatures estimated from this method are relatively consistent with other ground-based temperature measurements (Singer et al, 2003Hocking et al, 2004Hocking et al, , 2007Holdsworth et al, 2006;Stober et al, 2008). For details on the advantage and limitation of this method refer to Hocking et al (2004).…”
Section: Introductionsupporting
confidence: 70%
“…From our results, the summer to winter variation of meteor temperatures is around 40-50 K, which is comparable with the results of other studies. We compared the meteor temperatures with SATI OH and O 2 temperatures day by day, while previous studies (Hocking et al, , 2007Holdsworth et al, 2006) compared mean temperatures estimated from meteors over 2-7 day with those of other measurements. For the 54 simultaneously observed days in 2007, the correlations between our daily mean meteor temperatures and, SATI OH and O 2 rotational temperatures are 0.1 and 0.26, respectively.…”
Section: Temperature Estimationmentioning
confidence: 99%
“…While the CSU and URB climatologies show some differences, as much as 10 K in some small height-time intervals, the difference in the overall average of these climatologies is only ∼0.4 K. This difference is much smaller than the difference between the Na lidar climatologies and the PCL climatology. Hocking et al (2007) have compared temperature measurements from the Purple Crow Lidar, temperatures derived from airglow measurements of hydroxl and temperatures derived from the fading of meteor echoes using the CLOVAR radar. All three instruments were located within 20 km of each other.…”
Section: P S Argall and R J Sica: A Comparison Of Rayleigh And Somentioning
confidence: 99%
“…All three instruments were located within 20 km of each other. Using coincident nights of measurements for the radar and lidar (a data set biased to the summer months) Hocking et al (2007) found that in the 85 km region the temperatures were within 1 K of each other. In the 91 km region the lidar temperatures were ∼5±3 K cooler than the radar temperatures.…”
Section: P S Argall and R J Sica: A Comparison Of Rayleigh And Somentioning
confidence: 99%
“…Meteor radar temperatures offer the possibility of 24 h per day measurements and in all sky conditions (Hocking et al, 2007). Hall et al (2004) extrapolated the OH temperatures from 87 km to 90 km for the purpose of a multi-instrument derivation of 90 km temperatures over Svalbard based on the CIRA-86 and MSISE-90 models.…”
Section: Introductionmentioning
confidence: 99%